Ulti’em! Cuing between allies in Massive Online Battle Arena video games - Pratama, Ryu Rizky; Latief, Muhammad; Utami, Dayu Pratiwi; Ummah, Ilda Cholifatul; Hanafi, Muhammad Adib; Anfagata, Jetsa; Saputra, Nandha Indarto (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2024)
This research focuses on the use of participation cues in the communication and expression of players in MOBA games. The MOBA games studied are Mobile Legends: Bang Bang, League of Legends: Wild Rift, and Pokémon Unite. Participation cues are used to allow players to inform each other about the progress of the game. The qualitative descriptive method was used in this research. In answering the formulation problems, participation cue theory by Keating and Sunakawa (2010) was used, which was elaborated by Bartle (1996) about player types. The data in this study are textual and visual, consisting of verbal and non-verbal forms of communication. The data was collected using playing and documentation techniques, and then analysed using Spradley (1997). From the research conducted, it can be concluded that the most common participation cues used by players are verbal cues, which have the characteristics of Achiever players. Verbal cues are used by players to express themselves directly to players so that the goals they want to achieve together can be realised. This research uses the term 'participation cue' to invite further research into communication strategy in games.